Direct observation of reversible conversion and alloying reactions in a Bi2(MoO4)3-based lithium-ion battery anode. Issue 30 (12th July 2019) - Ruud, Amund; Sottmann, Jonas; Vajeeston, Ponniah; Fjellvåg, Helmer
Abstract : Bi2 (MoO4 )3 has been evaluated as an interesting anode material for application in lithium-ion batteries (LIBs). Abstract : Bi2 (MoO4 )3 has been evaluated as an interesting anode material for application in lithium-ion batteries (LIBs). When cycled in the voltage window of 0.01–2.50 V a specific charge capacity of more than 800 mA h g −1 is retained after 50 cycles. According to operando synchrotron X-ray diffraction (XRD) the long-range order is lost during the initial lithiation. Direct insight into the electronic changes during cycling is obtained from operando Bi L3- and Mo K-edge X-ray absorption near edge spectroscopy (XANES) data collected during the first 1.5 cycles. A redox pair with anodic reactions at 0.97 V and cathodic reactions at 0.59 V is ascribed to alloying of bismuth: 3Li + Bi ↔ 2Li + LiBi ↔ Li3 Bi. Likewise, reactions are ascribed to redox processes of Mo. Notably, the use of a cycling range limited to 2.00 V does not allow for a complete reoxidation of Mo, which in turn limits the reversibility of the Mo redox reactions.